Peran ChatGPT sebagai Asisten Pembelajran dalam Meningkatkan Efektivitas Pembelajaran Daring Mahasiswa Teknik Informatika - Pelealu, Fadel; Umboh, Putri; Kainde, Henry Valentino Florensius (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of Artificial Intelligence (AI) technology has significantly influenced various aspects of human life, including higher education. One of the most widely adopted AI innovations today is ChatGPT, a Large Language Model (LLM)-based chatbot capable of generating fast, interactive, and contextual responses according to user input. The emergence of ChatGPT has created new opportunities to support online learning activities, which have become increasingly important in higher education institutions. This study aims to analyze the role of ChatGPT as a learning assistant in improving the effectiveness of online learning for Informatics Engineering students. The research employed a Literature Review method by examining relevant scientific articles, conference proceedings, and academic publications obtained from Google Scholar, Scopus, IEEE Xplore, ScienceDirect, and SpringerLink. The research process consisted of topic identification, literature searching, source selection based on predetermined criteria, content analysis, and synthesis of findings. The results indicate that ChatGPT contributes to improving conceptual understanding, supporting self-directed learning, assisting academic problem-solving, and enhancing learning efficiency. In the field of Informatics Engineering, ChatGPT is widely utilized to support learning activities related to algorithms, programming, and code debugging. However, its implementation also presents several challenges, including information accuracy, technological dependency, and risks associated with academic integrity. Therefore, the use of ChatGPT should be accompanied by digital literacy, critical thinking skills, and responsible utilization to maximize its benefits in supporting effective online learning within higher education environments.